Optimisation of Production Parameters Used in Turning Waste Cooking Oil as Fuel - Karabas, Hulya (Asian Journal of Chemistry, 2013)
In the present study, waste cooking oil with low free fatty acids content was used as feedstock for producing biodiesel. Biodiesel was produced by alkaline-catalyzed transesterification process, which was designed according to the Taguchi method. Molar ratio alcohol/oil, catalyst concentration, reaction temperature and reaction time was chosen as control parameters. Taguchi method was used for optimizing the parameters used in methyl ester production. In experimental study, potassium hydroxide was used as catalyst 0.5 % in volume, molar ratio alcohol/oil (1/10), reaction temperature was 50 ºC and reaction time was 80 min. Catalyst concentration was found the most efficient parameter according to Taguchi method. Finally, the yield of produced waste cooking oil methyl ester was up to 98 % with the optimal conditions of the control parameters which were obtained by Taguchi method. As a result, it is thought that waste cooking oil that has many negative effects in terms of environment can be utilized as an economic and renewable energy source.